2015
DOI: 10.7314/apjcp.2015.16.2.627
|View full text |Cite
|
Sign up to set email alerts
|

Parecoxib: an Enhancer of Radiation Therapy for Colorectal Cancer

Abstract: Background: To study the effect of parecoxib, a novel cyclooxygenase-2 selective inhibitor, on the radiation response of colorectal cancer (CRC) cells and its underlying mechanisms. Materials and Methods: Both in vitro colony formation and apoptosis assays as well as in vivo mouse xenograft experiments were used to explore the radiosensitizing effects of parecoxib in human HCT116 and HT29 CRC cells. Results: Parecoxib sensitized CRC cells to radiation in vitro with a sensitivity enhancement ratio of 1.32 for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Parecoxib, a water-soluble prodrug which is biotransformed in the liver by enzymatic hydrolysis and converted into its active metabolite, valdecoxib, is a selective COX-2 inhibitor used to minimize postoperative pain in noncardiac surgeries. It is also the only selective NSAID marketed that allows parenteral administration [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parecoxib, a water-soluble prodrug which is biotransformed in the liver by enzymatic hydrolysis and converted into its active metabolite, valdecoxib, is a selective COX-2 inhibitor used to minimize postoperative pain in noncardiac surgeries. It is also the only selective NSAID marketed that allows parenteral administration [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we chose a different COX-2 inhibitor, parecoxib, to achieve chemopreventive and toxicological studies in vivo using the same animal model. Parecoxib is a water-soluble prodrug of valdecoxib [15,16] and is the only selective COX-2 inhibitor that can be administered parenterally, which may contribute to a different toxicological profile compared to other COX-2 inhibitors such as celecoxib [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Parecoxib is another important selective COX-2 inhibitor, with high postoperative pain control and less side effects ( 106 ). Treatment with parecoxib has exhibited a promising anticancer role in different types of human cancer ( 106 , 107 ).…”
Section: Upregulated Expression Of Mirnas By Cox-2 Selective Inhibitomentioning
confidence: 99%
“…Parecoxib is another important selective COX-2 inhibitor, with high postoperative pain control and less side effects ( 106 ). Treatment with parecoxib has exhibited a promising anticancer role in different types of human cancer ( 106 , 107 ). The latest research suggests that parecoxib inhibits the proliferation, migration and invasion of glioblastoma cells by upregulating miR-29c expression ( 108 ).…”
Section: Upregulated Expression Of Mirnas By Cox-2 Selective Inhibitomentioning
confidence: 99%
“…Accumulating data indicated that COX-2 inhibitors, the non-steroidal anti-inflammatory drugs, are promising chemoprevention and chemotherapeutic agents that may protect against breast, brain, lung, esophageal, colon, and oral tumors ( Dang et al, 2002 ; Menter, 2002 ). Of the COX-2 inhibitors, parecoxib is one of the most well-known COX-2 selective inhibitors, which had been developed as a highly efficient postoperative analgesia drug with low adverse reaction, and parecoxib treatment was shown to exert a potent anticancer role in multiple human cancers, including colorectal cancer ( Zagani et al, 2009 ; Xiong et al, 2015 ), esophageal adenocarcinoma ( Santander et al, 2012 ). It is worth noting that parecoxib treatment was capable of enhancing immunotherapy of brain tumors.…”
Section: Introductionmentioning
confidence: 99%